Optimization of banana sucker production using different macropropagation structures and substrates - Abel Sefasi; Mvuyeni Nyasulu; Khumbo Pute; Rowland Maganizo Kamanga; Eviness Nyalugwe; Lameck Matiki; Yamikani Gada; Joseph Chimungu (PLoS ONE, 2026)
Banana ( Musa spp .) production in Malawi is constrained by limited access to high-quality planting materials, restricting farm productivity. This study evaluated the effects of macro-propagation structures and substrates on growth and sucker production of banana cv. Williams, and examined the relationship between decapitated primary suckers and secondary sucker production. Field experiments tested three macro-propagation structures (standard chamber, standard chamber with black net, and mulched open bed) and three substrates (loam soil, rice husks, and sawdust). Growth parameters, including leaf number, plant height, root number, root length, and number of suckers harvested, were recorded, while regression, correlation, and principal component analyses were conducted. The standard chamber produced the tallest plants (20.50 ± 0.83 cm) and highest sucker number (102.22 ± 14.09), whereas sawdust and loam soil supported the highest sucker yields (85.33 ± 13.81 and 79.00 ± 11.95, respectively). Rice husks promoted the longest roots (11.49 ± 0.69 cm). The combination of standard chamber with sawdust maximized plant height (22.33 cm) and sucker yield (135.33). Regression analysis revealed a strong positive relationship between decapitated primary suckers and secondary sucker production (R² = 0.741, p < 0.001), confirming that decapitation enhances sucker proliferation. Principal component analysis showed that shoot and sucker traits were the main contributors to variation among treatments, while root traits varied inversely with aboveground growth. These results demonstrate that optimizing macro-propagation structures and substrates, together with sucker decapitation, can significantly improve banana sucker production, thereby increasing the availability of quality planting materials in Malawi.